Valor nutritivo de forrageiras de inverno e produção de silagem pré-secada - Silveira, Allan Patrick (2015)
This study evaluated the production and nutritional quality of temperate grasses: Oats White IPR 126 (ABR), Oats Black IAPAR 61 (AV), ryegrass Barjumbo (AZ) and rye Temprano (EC) by making haylage dry web at different growth stages: vegetative and reproductive. The experiment was conducted at the Federal Technological University of Paraná, Campus Two Neighbors April to September 2013 in an experimental area of 560m², divided into 32 plots of 16 m each. The seeding was done manually on April 27, 2013 in properly limed soil, the applied fertilizer was the NPK. The experimental design was randomized blocks (DBA) in a factorial scheme, assessing the cultivar and the phenological stage of the grasses. The treatments were the ABR grasses, AV, AZ and CE, the qualitative and quantitative differences were evaluated between them, and the phenological stages were vegetative (first and second cut) and reproductive: total (4X3) 12 treatments with 4 replicates . Silos were made in PVC microsilos (500 mm long by 100 mm diameter). We conducted three sections, two with the plants in vegetative stage and one in the reproductive stage. The first cut of the vegetative stage was held on 16 July 2013, a total of 80 days from sowing to the court. The second section of the vegetative stage was held on different dates: August 29 for ABR and September 11, 2013 AV, AZ and CE, and the court (reproductive stage) was similarly conducted on different dates: 10 August 2013 to Apr, August 15 to September 10 and AV for AZ and CE, totaling respectively, 105, 110 and 136 days after sowing. The cuts were made to ten inches from the ground to the ABR and AV cultivars and three inches to AZ and CE, this time was determined in relation to the plant structure to encourage the regrowth. The pre-drying introduced himself efficient for conservation of winter grasses and silage has managed to preserve the most of their quality. Higher yields of dry matter / ha was obtained in the stages of plants and no loss in nutritive value for silage at levels above 35% dry matter. The oat IAPAR 61 excelled in the production of dry matter compared to oat IPR 126, ryegrass and rye Barjumbo Temprano. The Barjumbo and rye Temprano ryegrass showed the best rates of nutritional value in court in vegetative stage of the plant.